Virtual informatics museum - Almeida, José Maria Fernandes (2008)
ALMEIDA, José M. F. Virtual Informatics Museum. In: PUTNIK, Goran D; CUNHA, Maria Manuela (Eds). Encyclopedia of Networked and Virtual Organizations (pp. 1785-1791). Information Science Reference, Hershey PA, USA, 2008. ISBN 159904885X.